Distribution of the Dispersed Phase in the Gas Cleaning Equipment with Pulsating Plug - Kozii I.S.; Plyatsuk L.D.; НuretsL.L. (Problems of the Regional Energetics, 2021)
The work is devoted to the reduction of the technogenic impact on the environment from the emissions of heat power engineering by using a highly efficient equipment for the complex purification of exhaust gases — a equipment with a regular pulsating plug (RPP). The aim of the study is the physical and mathematical description of the mechanisms of the process of capturing fine dust in a equipment with an on-load tap changer. This goal is achieved by describing the physical picture of the dust collection process in an experimental equipment with an on-load tap-changer; mathematical description of the condensation capture of fine dust; descriptions of the process of droplet distribution in the layer of turbulizing packing elements during upward movement of phases. As a result of calculations, an equation was obtained for determining the radius of a particle in the process of condensation of a vapor-gas-liquid system, which allows one to determine the further possibility of trapping particles due to the inertial or turbulent-diffusion mechanism in the device. An equation is obtained for calculating the diameter of liquid droplets formed during the crushing of liquid flows by turbulizing packing elements, which allows us to conclude that the phase contact surface is developed due to the pulsating movement of packing elements. Studies of the equipment with an on-load tap-changer allow us to speak about the possibility of its use for the complex cleaning of dust and gas emissions from heat power enterprises in order to reduce the negative impact on the environment.